Agave potatorum Zucc. growth promotion by free-living nitrogen-fixing bacteria - Bautista-Cruz, Martha Angélica; Martínez-Gallegos, Verónica (REVISTA TERRA LATINOAMERICANA, 2020)
The free-living nitrogen-f ixing bacteria (FLNFB) can be an important alternative to replace mineral fertilizers in agriculture. Agave potatorum Zucc, commonly known as “maguey tobalá”, is a wild species from which a highly demanded “mezcal” (liquor) is obtained and distinguished by its high quality. As it is a wild species, not much information is available referring to its agricultural management. This study assessed the effect of FLNFB inoculation on plant growth and solid soluble content (SSC) of the stem of A. potatorum plants under semi-controlled conditions and a randomized complete block design; three FLNFB (1) Burkholderia cepacia, (2) Flavobacterium sp., (3) Paenibacillus amylolyticus and a control (without FLNFB) were assessed in four blocks with 15 agave plants per block; each plant in the same block was randomly assigned to a different FLNFB. The plant growth variables assessed after 48 weeks were: plant height (PH), plant rosette diameter (ROD), plant stem diameter (PSD), unfolded leaves number (ULN), root volume (RV), root density (RD), stem dry biomass (SDB), total dry biomass (TDB), leaf area (LA) and SSC (°Bx). An analysis of variance and Tukey’s multiple range test for means separation (P ≤ 0.05) revealed that with respect to the control, B. cepacia increased RV 322.2%; ULN 42.6%; and SSC 72.9%. P. amylolyticus increased SDB 317.1%. B. cepacia, Flavobacterium sp., and P. amylolyticus increased the PSD approximately 50.3%; ROD 48.6%; LA 127.2%; and PH 51.8%. Flavobacterium sp. increased TB 164.8%. These results suggest that the FLNFB promoted growth of A. potatorum plants, making this environmentally friendly and inexpensive technology a good alternative for agave production.